2012
DOI: 10.1063/1.3682772
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory bubbles induced by geometrical constraint

Abstract: We show that a simple change in pore geometry can radically alter the behavior of a fluid-displacing air finger, indicating that models based on idealized pore geometries fail to capture key features of complex practical flows. In particular, partial occlusion of a rectangular cross section can force a transition from a steadily propagating centered finger to a state that exhibits spatial oscillations formed by periodic sideways motion of the interface at a fixed distance behind the moving finger tip. We chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 18 publications
6
47
0
Order By: Relevance
“…B. Thompson, A. L. Hazel and A. Juel of the channel height (de Lózar et al 2009;Pailha et al 2012;Hazel et al 2013). Thompson et al (2014) found that all finger propagation modes in partially occluded Hele-Shaw channels were qualitatively reproduced in an adapted version of the depthaveraged model used by McLean & Saffman (1981) to show that finite surface tension selects the half-width finger in unoccluded Hele-Shaw channels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…B. Thompson, A. L. Hazel and A. Juel of the channel height (de Lózar et al 2009;Pailha et al 2012;Hazel et al 2013). Thompson et al (2014) found that all finger propagation modes in partially occluded Hele-Shaw channels were qualitatively reproduced in an adapted version of the depthaveraged model used by McLean & Saffman (1981) to show that finite surface tension selects the half-width finger in unoccluded Hele-Shaw channels.…”
Section: Discussionmentioning
confidence: 99%
“…The subcritical symmetry-breaking bifurcation is also associated with oscillatory solutions, identified by Pailha et al (2012), who proposed a surface tension-based mechanism to explain their genesis. A fast local decrease in the cross-sectional curvature occurs when the interface of a finger passes over the edge of the occlusion to the less occluded region.…”
Section: Generic Behaviour Of the Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…These patterns are shed from the propagating front, that undergoes oscillations in width driven by the change in cross-sectional curvature of the interface as it crosses the edge of the block. This mechanism has been described in rigid constricted tubes [11,18,19] and is also the dominant mechanism in Fig. 1(b), where fingers are generated in the direction of the strongest depth gradient.…”
mentioning
confidence: 99%